Fizzy Sentiments: Coca-Cola and the Global Culture Industry - Jabbar, Tania (Glendon Journal of International Studies, 2016)
Abstract: This paper explores how the global culture industry shapes human conduct and values in the context of one of the world’s biggest brands: Coca-Cola. It is organized to answer the following questions: what is Coca-Cola’s public image? Who or what is creating the significance reflected in the product? To what extent is Coca-Cola a cultural sign in the global culture industry? Commodity fetishism allows Coca-Cola to be valued beyond its high-fructose content, and for its intrinsic ideologies. The central argument is that the company’s success is embedded in its manipulation of human needs. The Coca-Cola Company is a successful actor involved in the distribution and intensification of the global culture industry because it is a substitute religion that promotes fetishes, which satisfy worldview mythical values such as inclusiveness and peace. Through a structuralist theoretical framework, this study concludes that Coca-Cola’s consumption involves the absorption of symbols, mythologies, and fetishes fixated in the brand’s image for universality, which ultimately harbour sentiments that are easily worshipped like many religions are in the world. Résumé : Cet essai explore comment l’industrie de la culture globale façonne la conduite et les valeurs humaines dans le contexte d’une des plus grandes marques mondiales : Coca-Cola. Il répond aux questions suivantes : Quelle est l’image publique de Coca-Cola ? Qui ou quoi crée l’importance reflétée dans ce produit ? Dans quelle mesure est-ce que Coca-Cola est un signe culturel dans l’industrie de la culture globale ? Le fétichisme de la marchandise permet à Coca-Cola d’être valorisé au-delà de sa teneur en fructose et de ses idéologies intrinsèques. L’argument principal est que le succès de la compagnie est intégré dans leur manipulation des besoins humains. La compagnie Coca-Cola est un acteur accompli, impliqué dans la distribution et l’intensification de l’industrie de la culture globale parce que c’est une substitution de religion qui fait promotion des fétiches, qui donnent satisfaction aux valeurs mythologiques mondiales telles que l’inclusion et la paix. Au moyen d’un cadre théorique structuraliste, cette étude conclut que la consommation de Coca-Cola entraîne l’absorption de symboles, mythologies et fétiches fixés à même l’image de la marque d’universalité, ce qui, ultimement, entretient des sentiments qui sont facilement vénérés comme plusieurs religions le sont autour du monde.